TKPlate 1.0: An Open‐access platform for toxicokinetic and toxicodynamic modelling of chemicals to implement new approach methodologies in chemical risk assessment - Jean Lou C. M. Dorne; José Cortiñas‐Abrahantes; Fotis Spyropoulos; Keyvin Darney; Leonie Lautz; Jochem Louisse; George E. N. Kass; Edoardo Carnesecchi; A. K. Djien Liem; José V. Tarazona; Pierre‐André Billat; Rémy Beaudoin; et al. (EFSA Journal, 2023)
This publication is linked to the following EFSA Supporting Publications articles: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2023.EN-8441/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2023.EN-8440/full, http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2023.EN-8437/full